BRCA1/2 Mutation Types Do Not Affect Prognosis in Ovarian Cancer Patients. - Liontos, Michalis; Zografos, Eleni; Zoumpourlis, Panagiotis; Andrikopoulou, Angeliki; Svarna, Anna; Fiste, Oraianthi; Kunadis, Elena; Papatheodoridi, Alkistis Maria; Kaparelou, Maria; Koutsoukos, Konstantinos; Thomakos, Nikoloas; Haidopoulos, Dimitrios; et al. (Current Oncology, 2021)
Background: High grade serous ovarian carcinoma (HGSOC) is the most lethal type of epithelial ovarian cancer, with a prevalence of germline BRCA1/2 mutations as high as 20%. Our objective is to determine whether the location of mutations in the different domains of the BRCA1/2 genes affects the clinical outcome of HGSOC patients. Methods: A total of 51 women with BRCA1 or BRCA2 mutated ovarian cancer were identified. Progression-free survival (PFS) and overall survival (OS) were analyzed. Results: In our study cohort, 35 patients were carriers of germline mutations in BRCA1 and 16 in BRCA2. The median PFS time following completion of the primary therapy was 23.8 months (95% CI 20.1-27.5) and the median OS was 92.9 months (95% CI 69.8-116.1) in all BRCA carriers. After multivariate analysis, no significant association among the location or type of BRCA1/2 mutation with PFS or OS was identified. Notably, significant differences in PFS between carriers of identical mutations in the same BRCA gene were detected. Conclusions: Among HGSOC patients, BRCA1/2 carriers with mutations in different locations of the genes show no significant difference in survival outcomes, in terms of PFS and OS, suggesting the potential effect of other genetic abnormalities and co-contributing risk factors.